Repräsentative Demokratie in der Krise? - Walter, Christian (De Gruyter, 2013)
This volume contains presentations and discussions from a conference of the Association of German Constitutional Law Professors held in Kiel on 3-6 October 2012.
"Referate und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Kiel vom 3. bis 6. Oktober 2012."
Keywords: Democracy -- Congresses.; ART -- Study & Teaching.; Democracy.; Political Science.; Government - Non-U.S.; Law, Politics & Government.; Political Theory of the State.; Government - Europe.; Electronic books.; Conference papers and proceedings.